2022
DOI: 10.1101/2022.08.12.503780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipids Maintain Genomic Stability and Developmental Potency of Murine Pluripotent Stem Cells

Abstract: Lipids play vital roles in cellular homeostasis and regulate pluripotency of human stem cells. However, the impact of lipids on murine pluripotent stem cells is unclear. While Mek and Gsk3 inhibition supports the maintenance of murine embryonic stem cells in a homogenous naive state, prolonged culture in 2i results in aneuploidy and DNA hypomethylation that impairs developmental potential. Additionally, 2i fails to support derivation and culture of fully potent female ESCs. Here we find that mouse ESCs culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…However, extended Mek1/2 suppression of ESCs in this medium leads to aneuploidy, global DNA hypomethylation and loss of imprinting. This is typically more prominent for female ESCs, leading to rapid loss of pluripotency in early passages [ 15 , 16 , 23 , 24 ]. Our recent study has shown that supplementing the 2i/LIF medium with AX, can mitigate DNA hypomethylation and prevent loss of imprinting, thereby supporting the long-term culture of mESCs while preserving pluripotency [ 23 , 24 ].…”
Section: Lipids Play a Vital Role In Maintaining The Genome Stability...mentioning
confidence: 99%
See 4 more Smart Citations
“…However, extended Mek1/2 suppression of ESCs in this medium leads to aneuploidy, global DNA hypomethylation and loss of imprinting. This is typically more prominent for female ESCs, leading to rapid loss of pluripotency in early passages [ 15 , 16 , 23 , 24 ]. Our recent study has shown that supplementing the 2i/LIF medium with AX, can mitigate DNA hypomethylation and prevent loss of imprinting, thereby supporting the long-term culture of mESCs while preserving pluripotency [ 23 , 24 ].…”
Section: Lipids Play a Vital Role In Maintaining The Genome Stability...mentioning
confidence: 99%
“…This is typically more prominent for female ESCs, leading to rapid loss of pluripotency in early passages [ 15 , 16 , 23 , 24 ]. Our recent study has shown that supplementing the 2i/LIF medium with AX, can mitigate DNA hypomethylation and prevent loss of imprinting, thereby supporting the long-term culture of mESCs while preserving pluripotency [ 23 , 24 ]. In 2i/LIF cultures, the DNA methyltransferase 3 enzymes (DNMT3A, DNMT3B, DNMT3L), which add a methyl group to the carbon 5 position of cytosine residues in DNA — a process known as DNA methylation — are suppressed in ESCs.…”
Section: Lipids Play a Vital Role In Maintaining The Genome Stability...mentioning
confidence: 99%
See 3 more Smart Citations